2009
DOI: 10.1345/aph.1l511
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan in Cancer Patients with End-Stage Renal Failure

Abstract: We conclude that approximately two-thirds of the standard weekly irinotecan dosage regimen should be considered in patients with ESRF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…1D). In contrast, SN-38 was not dialyzable in previous studies (Venat-Bouvet et al, 2007;Czock et al, 2009), but they did not mention the specifications of the dialyzer used. There may be differences between the specifications of dialyzers used in this study and previous studies.…”
Section: Downloaded Frommentioning
confidence: 91%
See 2 more Smart Citations
“…1D). In contrast, SN-38 was not dialyzable in previous studies (Venat-Bouvet et al, 2007;Czock et al, 2009), but they did not mention the specifications of the dialyzer used. There may be differences between the specifications of dialyzers used in this study and previous studies.…”
Section: Downloaded Frommentioning
confidence: 91%
“…The pharmacokinetics of irinotecan in patients with mild renal impairment who had a creatinine clearance (Ccr) of 35 to 66 ml/min were similar to those in patients with normal renal function (de Jong et al, 2008). Although several case reports have examined the effects of more severe renal dysfunction requiring dialysis on the pharmacokinetics or toxicity of irinotecan (Venat-Bouvet et al, 2007;Czock et al, 2009), no prospective study has been performed; nevertheless, such rare patients are given irinotecan in clinical practice.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Both reports mention that by increasing the dose, prohibitive diarrhea was the consequence. 8,11 The worst outcome in higher irinotecan doses (above 125 mg/m²) was demonstrated in two other dialysis patients, where these dosages led to extreme GI toxicities and even death. 9 It can be concluded that irinotecan in terminal renal insufficiency should not be given at a dose above 50 mg/m².…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Only case reports on the pharmacology of irinotecan in patients with colon or rectal cancer are available at present. [7][8][9][10][11] We present the first case of combination chemotherapy in metastatic gastroesophageal cancer in a dialysis patient.…”
Section: Introductionmentioning
confidence: 99%